A comparative study of the behaviour of treated and untreated tyre crumb mortar with oil palm fruit fibre addition - Abd. Aziz, Farah Nora Aznieta; Bida, Sani Mohammed; Mohd. Nasir, Noor Azline; Jaafar, Mohd Saleh (Universiti Putra Malaysia Press, 2017)
An incorporation of waste tyre particles in concrete has been established to produce a green concrete. However, despite its advantages, strength reduction is an obvious handicap. To improve the strength, pre-treatments of the waste tyre particles and addition of Oil Palm Fruit Fibre (OPFF) were chosen and reported in this study. The addition of OPFF was to influence the internal structure in order to improve shrinkage and other strength properties. Performance of the composites in compressive, split tensile and flexural strengths, as well as shrinkage and microstructure were observed. Results showed better behaviour of the treated tyre crumb mortar rather compared to the untreated tyre, with the replacement of up to 40% by volume of the treated tyre crumb particles and 0.5- 1.0% OPFF addition by mass of cement content.